Uczniowie chińscy w szkolnictwie angielskim – pomiędzy tradycyjną socjalizacją a walką o „sukces” - Gmerek, Tomasz (Wydawnictwo Naukowe UAM, 2012)
The article is devoted to educational achievement of chinese pupils in english education. Special attention is paid to social, cultural and economic background of chinese students. It explores the extent to which these background factors are mediated by educational achievement and social mobility. Chinese pupils mainly from middle-class were not only highly motivated but also possesed the economic, social and cultural background to achieve educational and social success in England.
Chinese students in English schooling – between traditional socialization
Keywords: Chinese students; education; socialization; achievement; social success